Influence of protein coronas between carbon nanoparticles extracted from roasted chicken and pepsin on the digestion of soy protein isolate. (15th August 2022) - Song, Xunyu; Song, Yukun; Guo, Zixuan; Tan, Mingqian
Graphical abstract: Highlights: The CNPs from roast chicken could reduce the digestibility of soy protein isolate. The pepsin structure was changed and its fluorescence was quenched by the CNPs. The formation of protein coronas between CNPs and pepsin reduced the pepsin activity. Abstract: Food-derived nanoparticles are inevitably ingested with food matrices and may negatively affect digestion. In this study, the bio-distribution of carbon nanoparticles (CNPs) extracted from roasted chicken in the gastrointestinal tract was investigated. Their biological effects on the digestion of soy protein isolate (SPI) with pepsin were explored by spectroscopic, morphological, and enzymatic methods. In vitro simulated digestion results showed that the digestibility of SPI was decreased from 93.53% to 79.56% in gastric juice with 10% CNPs. The CNPs were able to significantly reduce the activity of pepsin and disrupt its secondary structure ( P < 0.05). Ultraviolet–visible spectrometry demonstrated that CNPs exhibited a physical absorption effect on pepsin and quenched its fluorescence in a static model. The results of zeta potential and atomic force microscopy proved that the CNPs formed a nanoparticle-protein corona structure with pepsin, which could affect the digestion of SPI.